Measuring gender segregation in emerging adulthood: why it matters how we ask - Kotvas, Kourtney; Strough, JoNell (Frontiers in Developmental Psychology, 2026)
IntroductionGender segregated peer groups serve as an important context of socialization. The prevalence of gender segregation has typically been assessed via peer nominations, but this method has limitations.MethodsThe current study introduces two new measures of gender segregation—actual time spent with same-gender peers and ideal amount of time spent with same-gender peers—and compares the prevalence of gender differences in gender segregation on each measure to an established peer nomination measure. College students (N = 332; 58.4% women; 78.9% White; ages 18–29, M = 19.97) completed an online survey.ResultsThe prevalence of gender segregation differed significantly depending on participant gender and measurement type, with men reporting more gender segregation than women on the actual time measure, whereas no gender differences were found for the peer nomination or ideal amount of time measures.DiscussionThese findings demonstrate that measurement choice can meaningfully shape researchers understanding of gender segregation. Relying solely on peer nominations may obscure important gender differences in peer interactions. By introducing new measures of actual and ideal time spent with same-gender peers, this study provides researchers with a behaviorally-based tool that can yield a more complete understanding of gendered social relationships and their developmental consequences across the lifespan.